The impact of multiple sclerosis onset symptom on cardiac repolarization - Mikkola, Alma (Brain Behav, 2017)
INTRODUCTION: Multiple sclerosis is associated with prolonged cardiac repolarization but the underlying physiology has remained unknown. In this study, we compared cardiac repolarization during the relapsing‐remitting multiple sclerosis (RRMS) disease course in patients with motor and sensory onset symptom. METHODS: Twenty‐five RRMS patients with motor and 33 RRMS patients with sensory onset symptom having 12‐lead electrocardiogram (ECG) recorded at the time of the first demyelinating event (ECG1) as well as at the later disease course (ECG2) were identified from the patient records. The average time interval between ECG1 and ECG2 was 8.6 ± 5.9 y. Heart rate‐corrected QT intervals reflecting cardiac repolarization were calculated by Bazett (QTcBaz), Fridericia (QTcFri), and Karjalainen (QTcKar) formulas. RESULTS: Heart rate‐corrected QT intervals as well as heart rate were similar in patients with motor and sensory onset symptom in ECG1. However, QTcBaz (p = .002), QTcFri (p = .019), and QTcKar (p = .026) were longer and heart rate was higher (p = .035) in patients with motor than sensory onset symptom in ECG2. Correspondingly, QTcBaz (p = .002), QTcFri (p = .033), and QTcKar (p = .043) prolonged and heart rate tended to increase (p = .060) during the disease course only in the patients with motor onset symptom. CONCLUSIONS: Cardiac repolarization prolonged and heart rate increased during the disease course in RRMS patients with motor but not with sensory onset symptom. This suggests different traits in RRMS according to its initial manifestation and also association of motor onset symptom with more unfavorable cardiovascular prognostic determinants.